Surveillance of SARS-CoV-2 immunogenicity: loss of immunodominant HLA-A*02-restricted epitopes that activate CD8+ T cells - Lopes-Ribeiro, Ágata; Oliveira, Patrícia de Melo; Retes, Henrique Morais; Barbosa-Stancioli, Edel Figueiredo; da Fonseca, Flávio Guimarães; Tsuji, Moriya; Coelho-dos-Reis, Jordana Grazziela Alves (Frontiers in Immunology, 2023)
Introduction and methods In this present work, coronavirus subfamilies and SARS-CoV-2 Variants of Concern (VOCs) were investigated for the presence of MHC-I immunodominant viral peptides using in silico and in vitro tools. Results In our results, HLA-A*02 haplotype showed the highest number of immunodominant epitopes but with the lowest combined prediction score. Furthermore, a decrease in combined prediction score was observed for HLA-A*02-restricted epitopes when the original strain was compared to the VOCs, indicating that the mutations on the VOCs are promoting escape from HLA-A2-mediated antigen presentation, which characterizes a immune evasion process. Additionally, epitope signature analysis revealed major immunogenic peptide loss for structural (S) and non-structural (ORF8) proteins of VOCs in comparison to the Wuhan sequence. Discussion These results may indicate that the antiviral CD8+ T-cell responses generated by original strains could not be sufficient for clearance of variants in either newly or reinfection with SARS-CoV-2. In contrast, N epitopes remain the most conserved and reactive peptides across SARS-CoV-2 VOCs. Overall, our data could contribute to the rational design and development of new vaccinal platforms to induce a broad cellular CD8+ T cell antiviral response, aiming at controlling viral transmission of future SARS-CoV-2 variants.